EVALUASI PEMBERLAKUAN KAMPUNG RAMAH ANAK DI RW 02 KELURAHAN MANGGARAI KECAMATAN TEBET JAKARTA SELATAN - Imawati, Sri (Universitas Muhammadiyah Jakarta, 2017)
The purpose of this study are (1) To determine the benefits of Enforcement of the Child Friendly Village, (2) To determine the activities Child Friendly Village, (3) To evaluate the enactment of the Child Friendly Village. The method used in this research is descriptive qualitative method. Data collection techniques using observation, interviews, documentation, and field notes. Then the data were analyzed by means of data reduction, data presentation, and conclusion. Program kid friendly village very positive benefit for all people in Manggarai urban Rw 02 Tebet, South Jakarta. The conclusion of this study are: (1) The activities hometown kid friendly are: landfill, early childhood, her lessons, (2) Hour children's learning, and hours of playing children, (3) Implementation of the program hometown kid friendly is good but must be evaluated so that the future is better and more perfect